Partnership in strategic positioning for e-learning implementation - Awidi, I.; Cooper, Martin; Pagram, J. (2011)
E-learning has been identified, and now an important influence in higher education delivery. Though African universities have identified the need, and are employing various means in achieving the full potential to increase access to higher education, the major limitation has been a dependable and reliable infrastructure. Current partnerships have not built robust infrastructure that can sustain the elearning programmes. The focus of most of the partnership programmes has been directed towards capacity building. This paper investigates the attempt of the one leading University in West Africa to achieve, an e-learning goal through the building of ICT infrastructure. Issues considered include, the nature of partnership, management approach, effects of partnership, and lessons learnt from the partnership. From the findings, it is opined that, the strategic approach for ICT challenged environment to implement e-learning successfully, is to partner strategically with ICT rich institutions with the resources. From the partnership, the institutions will not only build the infrastructure, but also build capacity, and create jobs for ICT personnel. African universities may partner ICT rich institutions, and take ownership of the infrastructure. This may promote more future collaboration and partnership in higher education delivery. For electricity power stability, the universities may start experimenting the use of Solar Energy and alternative energy resources. In conclusion it is recommended that, cultural issues that may affect the sustenance and maintenance of the infrastructure for long-term use should be well addressed by management.